Dressing Method for the Degasperis–Procesi Equation. Issue 2 (8th September 2016) - Constantin, Adrian; Ivanov, Rossen
Abstract : The soliton solutions of the Degasperis–Procesi equations are constructed by the implementation of the dressing method. The form of the one and two soliton solutions coincides with the form obtained by Hirota's method.